SiGeSn quantum well for photonics integrated circuits on Si photonics platform: a review. (3rd November 2022) - Olorunsola, Oluwatobi; Said, Abdulla; Ojo, Solomon; Stanchu, Hryhorii; Abernathy, Grey; Amoah, Sylvester; Saha, Samir; Wangila, Emmanuel; Grant, Joshua; Acharya, Sudip; Miller, Lucas; Rosler, Kyle; et al.
Abstract: Recent studies of SiGeSn materials and optoelectronic devices hold great promise for photonics integrated circuits (PICs) on Si platform featuring scalable, cost-effective, and power-efficient. Thanks to the breakthrough of low temperature material growth techniques, device-quality level materials have been grown, following by the demonstration of light-emitting diodes, photodetectors, and optically pumped and electrically injected band-to-band lasers. While the exciting developments in bulk devices were reported, the quantum wells (QWs) have been investigated targeting the dramatically improved and/or novel device performance via variety of quantum confinement effects. In this review, we summarize the recent progress on development of SiGeSn QWs, including the fundamental optical and transition studies and optoelectronic device applications. The inspirational results reveal the possibility of all-group-IV PICs with photonics and electronics monolithically integrated on a single-chip.